Retraction notice to “Effectiveness of grease interceptors in food service establishments for controlling fat, oil and grease deposition in the sewer system” [Sci. Total Environ. 912 (2024) 169441] - Nilufa Sultana; Felicity Roddick; Bruce Jefferson; Li Gao; David Bergmann; Jim Papalois; Mike Guo; Kyriakos Tzimourtas; Biplob Kumar Pramanik (Science of The Total Environment, 2026)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

RETRACTED: Effectiveness of grease interceptors in food service establishments for controlling fat, oil and grease deposition in the sewer system - Nilufa Sultana; Felicity Roddick; Bruce Jefferson; Li Gao; David Bergmann; Jim Papalois; Mike Guo; Kyriakos Tzimourtas; Biplob Kumar Pramanik (Science of The Total Environment, 2024)

Designing an automatic pollen monitoring network for direct usage of observations to reconstruct the concentration fields - Mikhail Sofiev; Jeroen Buters; Fiona Tummon; Yalda Fatahi; Olga Sozinova; Beverley Adams-Groom; Karl Christian Bergmann; Åslög Dahl; Regula Gehrig; Stefan Gilge; Andrea Kofol Seliger; Rostislav Kouznetsov; et al. (Science of The Total Environment, 2023)

Correction to: Developments in the classification and nomenclature of arthropod-infecting large DNA viruses that contain pif genes - Monique M. van Oers; Elisabeth A. Herniou; Johannes A. Jehle; Peter J. Krell; Adly M. M. Abd-Alla; Bergmann M. Ribeiro; David A. Theilmann; Zhihong Hu; Robert L. Harrison (Archives of Virology, 2023)

Developments in the classification and nomenclature of arthropod-infecting large DNA viruses that contain pif genes - Monique M. van Oers; Elisabeth A. Herniou; Johannes A. Jehle; Peter J. Krell; Adly M.M. Abd-Alla; Bergmann M. Ribeiro; David A. Theilmann; Zhihong Hu; Robert L. Harrison (Archives of Virology, 2023)
Viruses of four families of arthropod-specific, large dsDNA viruses (the nuclear arthropod large DNA viruses, or NALDVs) possess homologs of genes encoding conserved components involved in the baculovirus primary infection mechanism. The presence of such homologs encoding per os infectivity factors ( pif genes), along with their absence from other viruses and the occurrence of other shared characteristics, suggests a common origin for the viruses of these families. Therefore, the class Naldaviricetes was recently established, accommodating these four families. In addition, within this class, the ICTV approved the creation of the order Lefavirales for three of these families, whose members carry homologs of the baculovirus genes that code for components of the viral RNA polymerase, which is responsible for late gene expression. We further established a system for the binomial naming of all virus species in the order Lefavirales , in accordance with a decision by the ICTV in 2019 to move towards a standardized nomenclature for all virus species. The binomial species names for members of the order Lefavirales consist of the name of the genus to which the species belongs (e.g., Alphabaculovirus ), followed by a single epithet that refers to the host species from which the virus was originally isolated. The common names of viruses and the abbreviations thereof will not change, as the format of virus names lies outside the remit of the ICTV.

Co-pyrolysis of biosolids with lignocellulosic biomass: Effect of feedstock on product yield and composition - Nimesha Rathnayake; Savankumar Patel; Ibrahim Gbolahan Hakeem; Jorge Pazferreiro; Abhishek Sharma; Rajender Gupta; Catherine Rees; David Bergmann; Judy Blackbeard; Aravind Surapaneni; Kalpit Shah (Process Safety and Environmental Protection, 2023)

Production of H2 and CNM from biogas decomposition using biosolids-derived biochar and the application of the CNM-coated biochar for PFAS adsorption - Savankumar Patel; Mojtaba Hedayati Marzbali; Ibrahim Gbolahan Hakeem; Ganesh Veluswamy; Nimesha Rathnayake; Kamrun Nahar; Shivani Agnihotri; David Bergmann; Aravind Surapaneni; Rajender Gupta; Abhishek Sharma; Kalpit Shah (Waste Management, 2023)

Review of influence of critical operation conditions on by-product/intermediate formation during thermal destruction of PFAS in solid/biosolids - Jianhua Zhang; Li Gao; David Bergmann; Tamara Bulatovic; Aravind Surapaneni; Stephen Gray (Science of The Total Environment, 2023)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Characterization of the Ecdysteroid UDP-Glucosyltransferase (egt) Gene of Anticarsia gemmatalis Nucleopolyhedrovirus - Júlio Carlyle Macedo Rodrigues; Marlinda Lobo De Souza; David O'reilly; Lucas Malard Velloso; Francisco José Rivera Pinedo; Fernando Barcellos Razuck; Berghem Ribeiro; Bergmann Morais Ribeiro (Virus Genes, 2001)

Enzymology of the oxidation of ammonia to nitrite by bacteria - Alan B. Hooper; Todd Vannelli; David J. Bergmann; David M. Arciero (Antonie van Leeuwenhoek, 1997)